Impact of chemical treatment on compression properties of Pentaclethra macrophylla /Arachis hypogaea hybrid composite for structural applications - Peter Okechukwu Chikelu; Paul Chukwulozie Okolie; Kingsley Chidi Nweke; Leo Aganyi Morga; Tochukwu Obialo Nwokeocha (FKIP - Universitas Pahlawan Tuanku Tambusai, 2025)
Lately, there's been a growing interest in replacing synthetic fibers with natural ones for composite materials, mainly because of environmental concerns. However, natural fiber composites face a significant challenge: they struggle with poor bonding to hydrophobic matrices due to their hydrophilic nature, which leads to subpar mechanical properties. Fortunately, this issue can be addressed through chemical treatment. In this study, fibres were extracted from the fruits of Arachis hypogaea and Pentaclethra macrophylla, then treated with NaOH solutions at concentrations of 2%, 4%, 6%, 8%, and 10%. These were then made into composites, subjected to compression testing, and analyzed using ANOVA and regression analysis. The results showed that the compression strength and yield strength peaked with the 6% NaOH treatment, increasing by 61.6% and 75.4%, respectively. The ANOVA results indicated a P-value below the significance level of 0.05 for both compression strength and yield strength, suggesting that the treatment significantly affects these properties. However, the P-value for Young's modulus was above the significance level, indicating that the treatment did not significantly impact it. Overall, the research suggests that a moderate alkaline treatment of these fibers can enhance the compression properties of hybrid natural fiber composites, making them suitable for load-bearing structural applications.